169k views
4 votes
Which equation correctly uses point (–2, –6) to write the equation of this line in point-slope form? Y – 6 = y minus 6 equals StartFraction 5 Over 2 EndFraction left-parenthesis x minus 2 right parenthesis.(x – 2) y – 6 = y minus 6 equals StartFraction 2 Over 5 EndFraction left-parenthesis x minus 2 right parenthesis.(x – 2) y + 6 = y plus 6 equals StartFraction 2 Over 5 EndFraction left-parenthesis x plus 2 right parenthesis.(x + 2) y + 6 = y plus 6 equals StartFraction 5 Over 2 EndFraction left-parenthesis x plus 2 right parenthesis.(x + 2)

User Bneely
by
6.4k points

2 Answers

3 votes

Answer:

Option D y + 6 = y plus 6 equals StartFraction 5 Over 2 EndFraction left-parenthesis x plus 2 right parenthesis.(x + 2)

Explanation:

User Anton Ashanin
by
6.3k points
4 votes

Answer:

Part 1)
y+6=(2)/(5)(x+2)

Part 2)
y+6=(5)/(2)(x+2)

Explanation:

The equation of the line in point slope form is


y-y1=m(x-x1)

we're going to analyze two cases

First case


Point\ (-2,-6)


slope\ m=(2)/(5)

substitute


y+6=(2)/(5)(x+2)

therefore

y plus 6 equals StartFraction 2 Over 5 EndFraction left-parenthesis x plus 2 right parenthesis

Second case


Point\ (-2,-6)


slope\ m=(5)/(2)

substitute


y+6=(5)/(2)(x+2)

therefore

y plus 6 equals StartFraction 5 Over 2 EndFraction left-parenthesis x plus 2 right parenthesis

User Drew C
by
6.2k points